MORPHOLOGIC-GENETIC PECULIARITIES OF SOILS IN MOUNTAIN MEADOWS OF THE NORTHERN URAL - Ye. V. Zhangurov; A. A. Dymov; Yu. A. Dobrovskiy (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
The peculiar morphology and physical-chemical properties of soils in mountain meadows of the Northern Ural are shown. From the position of the latest “Classification and Diagnostics of Soils in Russia” (2004) these soils are referred to 3 different types including the gray-humus (trunk of organo-accumulative soils), illuvial-humus-ferruginous soddy podburs (trunk of Al-humus soils) and gray-humus litozems (trunk of litozems)